Means of Tax Potential, Economic Security, Innovation and Digitalization in Economic Development - Safarov Giyosiddin Abdullaevich; Askarova Mavluda Turobovna; Khadzhayev Khabibulla Sagdullaevich; Rakhimov Eshmurad Normuradovich (International Journal on Economics, Finance and Sustainable Development, 2022)
Currently we are facing the widespread use of innovation and information technology in business processes. Due to the fact that there are situations that violate the law, leading to the loss of potential tax revenues, including local taxes. The government must be able to develop tax policies that can maximize the potential for tax revenue without hindering business growth and innovation. This study attempts to analyze the potential expansion of tax capacity. This article analyzes the tax potential, taking into account economic security, innovation and digital transformation of the economy. There have been reflected the results of scientific research in the field of forming the concept of tax potential and the main relationships between the varieties of tax potential.